La céramique du site néolithique de Contres “ Le Château-Gabillon ” (Loir-et-Cher) au sein de la culture de Chambon - Jean-Marc Pierrat (Revue Archéologique du Centre de la France)
The site of Château-Gabillon at Contres (Loir-et-Cher) is one of the most important of the Chambon culture: it is especially based on its ceramics that Roland Irribarria confirmed the uniqueness of this entity compared to the Cerny culture. This article makes a systematic study (morphology, decor, technology) of the bulk of the ceramic material on this site to move from qualitative to quantitative data and thus clarify the definition of the Chambon culture.These data are then compared to the first proposals for the development of Chambon ceramics to locate Contres among its stages. These comparisons result in the presentation of different hypotheses on the development of transformed quadrilateral and oval openings, which are abundant in this production, then on the formation of the Chambon culture in the Loire basin.